Fuzzy AHP for 3PL supplier’s performance evaluation considering risk (2017)
The 3PL logistic providers influence directly the global performance of the supply chain and business management success. This provider selection involves a detailed and careful study of different criteria. However, although the selection procedure had been appropriate, it is very important to analyze the benefits, advantages and disadvantages that the providers offer to the company. Once the provider is selected, an evaluation is required to allow the company to monitor the provider performance.On the other hand, the supply chain risk management is an issue with huge importance, from the academic perspective and the practical orientation. According to the literature, one of the main risks is the operational risk. Considering these a multicriteria methodology is proposed to evaluate 3PL performance, given that the operational risk is considered into the whole company process. The proposed model is based in a FAHP and validated in a manufacturing Colombian company for a freight land transport provider.